Bioprocesso, modelagem matemática e potenciais de aplicações do permeado de soro de queijo desproteinizado e levedura Kluyveromyces marxianus CCT 4086 - Maestre, Keiti Lopes (2020)
One of the by-products generated by the dairy industries is the deproteinized cheese whey permeate (DCWP), which has a high organic load, due to its high content of lactose and mineral salts. In order to transform dairy residues and minimize the environmental impacts that they can cause if incorrectly discarded in the environment, it is sought, through the application of biotechnology, to develop new products using dairy residues as raw materials. Therefore, when aiming at industrial scale production, it is essential the comprehension of the effects of experimental fermentation conditions, especially when it comes to the formation of bioethanol and/or bioproducts. Thus, the construction of mathematical models that describe bioconversion and assist in the optimization of processes is fundamental for increasing the yield of reactions. In this perspective, the general aim of this research was to evaluate the potential of the development of optimized and modeled bioprocess of the production of bioethanol from cheese whey permeate (DCWP) and Kluyveromyces marxianus CCT 4086 covering the concept of biorefinery. In addition, to perform the development and validation of a new mathematical model to describe the fermentation process of this yeast. For that, a 2³ factorial experimental design and a central rotational composite design for the biotransformation of the DCWP into bioethanol and other bioproducts were evaluated. Among the experimental assays, the largest bioconversions occurred with 88 g L-1 of lactose, in which the assay 1 (29 °C and pH 4.5) was the best condition, obtaining 50.65 g L-1 of bioethanol after 45 h of reaction, followed by the assays 20, 21 and 22 (30 ºC and pH 3.5) with an average ethanol concentration of 47.83 g L-1 in 40 h. In all assays, there were also galactooligosaccharides or organic acids production. Aiming at a model development that represented this fermentation process, two phenomenological models of the literature were analyzed and tested, and a new model was proposed. The kinetic parameters of the models were adjusted from a set of experimental data from the assays (1 and 5) under the same pH and temperature conditions (29 °C, pH 4.5). The model which better represented the bioconversion process was the proposed mathematical model, because it considers the effects of growth inhibition by the substrate and the cell death phase, incorporating the effects of releasing residual bioethanol during the cell growth phase. Thus, it is proven the potential of DCWP as a raw material for biotransformations and the formation of an integrated and sustainable process of a biorefinery from the dairy industry.